Electro‐optic Polymer Ring Resonator Modulator on a Flat Silicon‐on‐Insulator. Issue 6 (6th November 2017) - Qiu, Feng; Spring, Andrew M.; Hong, Jianxun; Miura, Hiroki; Kashino, Tsubasa; Kikuchi, Takamasa; Ozawa, Masaaki; Nawata, Hideyuki; Odoi, Keisuke; Yokoyama, Shiyoshi
Abstract: Optical polymers are a promising material of choice in the development of hybrid silicon photonics devices. Particularly, recent progress in electro‐optic (EO) active polymers has shown a strong Pockels effect. A ring resonator modulator is a vital building block for practical applications, such as signal processing, routing, and monitoring. However, the properties of the hybrid silicon and EO polymer ring modulators are still far from their theoretical limits. Here, we demonstrate a unique design of a hybrid ring resonator modulator simply located onto a silicon‐on‐insulator (SOI) substrate. Extra doping and etching of the SOI wafer is not required, even so we measured an in‐device electro‐optic coefficient r33 = 129 pm/V. The ring modulator exhibited a high sensitivity of the electrically tunable resonance, which enabled a 3 dB bandwidth of up to 18 GHz. The proposed technique will enable efficient mass‐production of the micro‐footprint modulators and promote the development of integrated silicon photonics. Abstract : A unique electro‐optic polymer ring modulator on a SOI substrate, free of any etching and additional doping, has been demonstrated. The device exhibits a record high in‐device electro‐optic coefficient of 129 pm/V. The bandwidth of 18 GHz is competitive with state‐of‐the‐art plasma dispersion‐based ring devices. The proposed technique will enable efficient mass‐production of the micro‐footprint modulators and promote the development of integrated silicon photonics.